Infantile Liver Failure as the Initial Manifestation of SCYL1-Related CALFAN Syndrome: A Case Report and Literature Review - Deepika Yadav; Nishant Wadhwa; Megha Sharma (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background: CALFAN (Cholestasis, Acute Liver Failure, and Neurodegeneration) syndrome is a rare autosomal recessive disorder caused by biallelic pathogenic variants in SCYL1 (SCY1-like pseudo-kinase 1). It is classically associated with low or normal gamma-glutamyl transpeptidase (GGT) cholestasis, infection-triggered acute liver failure (ALF), and progressive neurodegeneration. Because neurological and skeletal manifestations may be absent during the first hepatic presentation, early diagnosis can be missed unless the hepatic phenotype is recognized. Case: We describe a 9-month-old female infant born to third-degree consanguineous parents who developed fever-triggered cholestatic jaundice and ALF. Structural biliary disease, viral hepatitis, and common metabolic disorders were excluded. Whole-exome sequencing revealed a homozygous pathogenic nonsense variant in SCYL1 (c.1567C>T; p.Arg523*), consistent with autosomal recessive CALFAN syndrome. No neurological, neuroimaging, or skeletal abnormalities were present at initial presentation. The clinical course was notable for persistent hyperbilirubinemia and a family history of sibling death from infantile liver failure. Discussion: This case adds to the SCYL1 spectrum by demonstrating isolated infantile ALF without neurological features at presentation, a severe hepatic phenotype with persistent cholestasis, and a novel homozygous null variant in a consanguineous family. Conclusion: SCYL1 deficiency should be considered in infants with fever-triggered ALF and low/normal-GGT cholestasis, even when neurological and skeletal signs are absent. Early genomic testing, systematic exclusion of low-GGT cholestasis mimics, longitudinal neurological surveillance, timely transplant referral, and recurrence-risk counselling are essential.